(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The present paper focuses on the Ecological study of Earthquake. Bond has expressed concerns about deforestation, pollution, and the impact of urbanization on the natural habitats of animals. He has advocated for the protection of wildlife and the preservation of natural spaces for future generations. He has encouraged his readers to develop a deep appreciation for the natural world and to take active steps to protect and preserve the environment. Bond’s literary contributions have played a significant role in raising awareness about environmental issues in India. Bond is against the unsystematic development which is destroying the nature. The outcome of that can be in the form of earthquake, tsunami and other natural disasters.